2020
DOI: 10.1016/j.semcancer.2019.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell stemness, epithelial-to-mesenchymal transition, and immunoevasion: Intertwined aspects in cancer metastasis

Abstract: Recent advances in tumor immunology, fostered by dramatic outcomes with cancer immunotherapy, have opened new scenarios in cancer metastasis. The cancer stemness/mesenchymal phenotype and an excess of immune suppressive signals are emerging as Intertwined aspects of human tumors. This review examines recent studies that explored the mechanistic links between cancer cell stemness and immunoevasion, and the evidence points to these key events in cancer metastasis as two sides of the same coin. This review also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 115 publications
(175 reference statements)
0
19
0
1
Order By: Relevance
“…Muhammad et al revealed that c-Fos overexpression promotes EMT, cell stemness, and tumor growth when compared with control cells [ 28 ]. Cancer cells with increased stemness have stronger self-renewal and tumorigenesis abilities and contribute to adverse clinical outcomes [ 29 ]. Previous studies illustrated that FOXD1 can regulate the stemness of mesenchymal glioma stem cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muhammad et al revealed that c-Fos overexpression promotes EMT, cell stemness, and tumor growth when compared with control cells [ 28 ]. Cancer cells with increased stemness have stronger self-renewal and tumorigenesis abilities and contribute to adverse clinical outcomes [ 29 ]. Previous studies illustrated that FOXD1 can regulate the stemness of mesenchymal glioma stem cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…6f), it was suggested that drug resistance was related to immune response in glioma patients. It has also been reported that immune response and immune genes like B7H3 and Tim3 can contribute to the stemness and drug resistance [21,22]. Then, the relationship between risk signature and immune checkpoints, including B7H3, B7H4, Tim3, PD1, and PDL1 were analyzed [23,24].…”
Section: Potential Mechanisms Of Drug Resistance In Gliomamentioning
confidence: 99%
“…PD-L1, also known as CD274 or B7-H1, is a transmembrane protein physiologically expressed on the plasma membrane of antigen presenting cells and aberrantly expressed by tumor cells, supporting tumor immune evasion [ 1 ]. Tumor PD-L1 expression can be constitutive or acquired [ 2 ]. Genetic/epigenetic alterations, deregulated activation of oncogenic signaling pathways and stimuli from microenvironment [ 2 ] are among the causes of aberrant expression of such an immune modulatory ligand in cancer cells.…”
Section: Introductionmentioning
confidence: 99%